The evolution of the land developers' industry in a planned city: An agent based simulation model - Jonatan Almagor; Itzhak Benenson; Daniel Czamanski (European Regional Science Association (ERSA), 2014)
The paper presents agent-based model and simulations of the evolution of land developers' industry in a city regulated by a land use plan. We start with developers who are homogeneous in terms of wealth and simulate their economic growth as they make investments in lands and accumulate profits from construction. Over time some developers accumulate wealth enabling them to make investments and to take risks. We demonstrate that the introduction of advantage to size in purchasing parcels of land for future development and obtaining construction permits create a positive feed-back effects that increases the divergence between big and small developers. The interaction between developers' decisions regarding the location of land purchases and planner's approvals of piecemeal construction permits and comprehensive updates of zoning result in bifurcations of city structure that occur at times of plan modification and leads to a polycentric city.
Keywords: 330; Developers' Industry; Agent Based Model; Urban development; Urban modeling